Analysis of Parental Involvement in the Formation of Children's Character at Primary School Age - Sipahutar, Frengki; Sihite, Irma Ropianti; Syahrial, Syahrial (Journal of Digital Learning and Education, 2024)
This study explores the influence of parental involvement on the character development of elementary school-aged children, focusing on how different forms of parental engagement shape positive character traits. Utilizing a literature review methodology, this research synthesizes and analyzes empirical studies to provide a comprehensive understanding of the connection between parental involvement and children's character formation at this crucial developmental stage. Findings indicate that parental involvement plays a pivotal role in shaping children's character. Positive engagement from parents correlates with enhanced character development, while insufficient or negative involvement tends to impede the growth of positive character traits. The study underscores that the development of children's character is a collaborative endeavor involving parents, schools, and the wider community, highlighting the importance of a united approach in nurturing well-rounded individuals.